Atomic structure and physical properties of peridotite glasses at 1 bar - Le Losq, Charles; Sossi, Paolo A. (Frontiers in Earth Science, 2023)
Earth’s mantle, whose bulk composition is broadly peridotitic, likely experienced periods of extensive melting in its early history that formed magma oceans and led to its differentiation and formation of an atmosphere. However, the physical behaviour of magma oceans is poorly understood, as the high liquidus temperatures and rapid quench rates required to preserve peridotite liquids as glasses have so far limited their investigation. In order to better characterize the atomic structure and estimate the physical properties of such glasses, we examined the Raman spectra of quenched peridotite melts, equilibrated at 1900 °C ± 50 °C at ambient pressure under different oxygen fugacities (fO2), from 1.9 log units below to 6.0 log units above the Iron-Wüstite buffer. Fitting the spectra with Gaussian components assigned to different molecular entities (Q-species) permits extraction of the mean state of polymerisation of the glass. We find that the proportions of Q1 (0.36–0.32), Q2 (0.50–0.43), and Q3 (0.16–0.23) vary with Fe3+/FeTOT (FeTOT = Fe2+ + Fe3+), where increasing Fe3+/FeTOT produces an increase in Q3 at the expense of Q2 at near-constant Q1. To account for the offset between Raman-derived NBO/T (2.06–2.27) with those determined by assuming Fe2+ exists entirely as a network modifier and Fe3+ a network former (2.10–2.44), ∼2/3 of the ferric iron and ∼90% of the ferrous iron in peridotite glasses must behave as network modifiers. We employ a deep neural network model, trained to predict alkali and alkaline-earth aluminosilicate melts properties, to observe how small variations in the atomic structure of peridotite-like melts affect their viscosity. For Fe-free peridotite-like melts, the model yields a viscosity of ∼ −1.75 log Pa s at 2000 °C, similar to experimental determinations for iron-bearing peridotite melts. The model predicts that changes in the peridotite melt atomic structure with Fe3+/FeTOT yield variations in melt viscosity lower than 0.1 log Pa s, barely affecting the Rayleigh number. Therefore, at the high temperatures typical of magma oceans, at least at 1 bar, small changes in melt structure from variations in oxidation state are unlikely to affect magma ocean fluid dynamics.